investigation Of The Behavior Of Gusset Plate Welded Slotted Stainless Steel Tubular Members Under Axial Tension - Kıymaz, Güven; SEÇKİN, EDİP (Crc Press-Taylor & Francis Group, 6000 Broken Sound Parkway Nw, Ste 300, Boca Raton, Fl 33487-2742 USA, 2012)
In this paper, an experimental study on the behaviour of slotted end tubular member tension connections in stainless steel is presented. The failure of slotted end tension connections is mostly governed by fracture near the slotted end where local peak stress concentrations develop due to shear lag. Within the connected region, shear lag causes the unconnected peripheral region of the hollow section to lag behind the welded region in resisting the axial tensile forces. Experiments were conducted on slotted and gusset plate welded tubular member connections in stainless steel. Both circular and box section members were considered in the test program. 20 specimens were tested under concentrically applied axial tensile forces for varying tube-to-gusset plate weld lengths. Load-deformation curves were obtained and comparisons were made in terms of strength and ductility. The results obtained from the study were then critically examined and compared with currently available design guidance for slotted gusset plate welded tubular end connections. It is noted that no specific rules exist in international specifications on structural stainless steel which cover the design of such connections. Therefore, the results of this study are compared with the existing design rules for carbon steel.
Keywords: Structural Design; Shear Lag; Connection; Yapısal Tasarım; Makaslama Gecikmesi; Bağlantı